EXPLORATION OF ISLAMIC RELIGIOUS EDUCATION STRATEGIES IN ENHANCING ADOLESCENT MENTAL RESILIENCE - Khairanis, Retisfa; Aldi, Muhammad; Al Aziz, Sulthan (Prodi Pendidikan Agama Islam STAI Darul Falah, 2026)
Muslim adolescents frequently face various pressures and challenges that affect their mental health. Islamic religious education can improve adolescents' mental resilience by teaching religious values and spiritual practices. This research aims to explore effective Islamic religious education strategies for enhancing adolescents' mental resilience. This research uses qualitative methods with in-depth interviews and document analysis to collect data from teachers and students involved in the Islamic religious education program. The results showed that Islamic religious education strategies, such as teaching faith values, spiritual practices such as prayer and dhikr, and social support from the community, can help improve adolescents' mental resilience. These strategies help adolescents develop stress-coping skills and maintain mental balance. This research concludes that Islamic religious education can improve adolescents' mental resilience through comprehensive and religious values-based strategies. Thus, this study contributes to developing educational programs that are more effective in supporting adolescents' mental well-being.